The Effect of Chemotherapy in Gestational Trophoblastic Disease on Infertility: A Review on Pathophysiologic Mechanism - Eslamnik , Parvinsadat; Moghaddasi, Mana; Malmir, Ali; Sadeghi-Goughari, Bahar; Javan, Mohammad Reza; Ebrahimi, Maryam (Archives of Medical Laboratory Sciences, 2021)
Today, young women infertility through chemotherapy has become a global challenge. Chemotherapy destructs the malignant cells by reactive oxygen species (ROS) production and inflammatory factors secretion; these factors can also destruct the ovarian and uterine cells. Infertility usually happens as a result of ovarian and uterine cells apoptosis, as well as dysfunction in these organs. Signaling pathways activated by chemotherapy lead to increased activation of follicles and depletion of the follicular pool. In addition, excessive secretion of sex hormones leads to follicles activation and infertility in women. Mesenchymal stem cells (MSC) use have been reported to be a great help in restoring the function of ovarian and uterine cells. On the other hand, they can regulate sex hormone secretion. Finally, the use of MSCs as a suitable treatment strategy can help restore the function of reproductive cells and treat infertility. *Corresponding Author: Maryam Ebrahimi; ORCID iD: 0000 0001 9685 7882; Email: drmkhoddami@yahoo.com Please cite this article as: Eslamnik P, Moghaddasi M, Malmir A, Sadeghi-Goughari B, Javan MR, Ebrahimi M. The Effect of Chemotherapy in Gestational Trophoblastic Disease on Infertility: A Review on Pathophysiologic Mechanism. Arch Med Lab Sci. 2021;7:1-8 (e8). https://doi.org/10.22037/amls.v7.34369